Topical issues of institute of protection of the civil rights (Journal of actual problems of jurisprudence, 2018)
In this article it is considered topical issues of institute of protection of the civil rights. The author during research comprehensively considered concept of protection of the civil rights, in detail stopped on studying of formation of institute of protection of the civil rights. Legal bases of institute of protection of the civil rights are analysed and ways of protection of the civil rights are considered.Key words: protection of the civil rights, self-defense, subjective right, protection property right, protection of the real rights.